P081 Quick response codes for digital patient information leaflets in a rheumatology department: a quality improvement project. (23rd April 2022) - Zubairi, Rumaisa; Suhaimi, Ak Muhd Adiib Pg; Olsson, Lewis; Smyth, Rachel; Baxter, Derek; Laws, Arrianne; Perry, Martin E
Abstract: Background/Aims: Many rheumatology departments provide patients with physical copies of patient information leaflets (PILs). Quick response (QR) codes are a widespread simple means of distributing electronic information, involving delivery of digital information directly to a user subsequent to scanning the code with a smartphone camera. Advantages include reduced paper burden, instant updates and usage monitoring, creating great possibilities for their implementation in healthcare settings. Aim: To design and implement a QR code poster to provide electronic versions of PILs given to rheumatology patients. Methods: We met with senior clinicians and nurses to understand limitations of the current paper leaflet system and the desire for a digital alternative. A pilot questionnaire was then offered to patients attending clinics over two weeks to gauge attitudes to QR codes and identify PILs they had most interest in, in line with patient-centred care. Subsequent to a positive response, possible QR code management systems were investigated to select a platform with dynamic QR codes allowing tracking of usage metrics. A poster was designed, with eight QR codes leading to PILs from Versus Arthritis focusing on lifestyle aspects of rheumatic disease, as a reflection of both patient interest and clinician desire. Posters were displayed in clinic waiting areas to allow patients to scan them at their convenience. Clinicians were advised to signpost patients towards the QR codes to maximise use. Smaller copies of the poster were also made available for clinicians to distribute directly to patients at clinics, and appended to patient letters. Results: 14 patients completed the pilot questionnaire. Despite clinicians' regular distribution of paper leaflets, 35.7% reported they had never read a PIL. 42.9% of patients were more likely to read information about their condition on their phone rather than from a paper leaflet. 35.7% would like to scan a QR code to get digital information leaflets on their phone. Patients were almost equally interested in PILS about lifestyle (78.6%) and their diagnosed condition (78.6%) as medications (71.4%). PIL topics patients most commonly expressed an interest in included diet (71.4%), footcare (64.3%), pain (64.3%), fatigue (64.3%), complementary and alternative medicine (57.1%), emotional wellbeing (50%), gadgets and equipment for arthritis (50%) and keeping active (50%). QR codes leading to relevant PILs were thus selected for inclusion on the poster. Conclusion: There is a clear demand for digital PILs both from patients and clinicians. This ongoing quality improvement project has been successful in planning, designing and implementing a QR code poster to enhance patient access to information about lifestyle implications of rheumatic disease. Roll out of the posters has been successful and the project now requires monitoring of the uptake and usage pattern to further refine the delivery of digital QR code PILs. Disclosure: R. Zubairi: None. A. Muhd Adiib Pg Suhaimi: None. L. Olsson: None. R. Smyth: None. D. Baxter: None. A. Laws: None. M.E. Perry: Honoraria; AbbVie, Celltrion Healthcare, Gilead, Lilly, Biogen, Jaansen, Fresenius Kabi.